KHILAFAH, KESULTANAN, DAN KEPEMIMPINAN DALAM PERSPEKTIF ISLAM - Wahyuddin, Wahyuddin (Jurnal Pendidikan Kreatif, 2023)
Khilafah is one formof government that once existed in the historical and civilizational trajectory of Muslims in the world. Allah and His apostles, does not directly mention the model of government that must be formed by Muslims. Even after the death of the Messenger of Islam the Muslims in Medina at that time only committed them selves in determining who would replace the position of the prophet Muhammad as the head of the state of Medina, including the non-apostolic spiritual office he was in. However, in al-Qur'an and al-hadith found a number of designations for leaders such as the Khalifah, Malik, Wali, Shulthân, Ulil Amri, Imam, Ra`inand Amir. In al-hadith it self, the apost leclearly states the limits of obedience to the leader, there sponsibilities and functions of the leader and the people obligations towards the leader. This paper examines the sematters through content analysis, especially of text sabout ladership contained in the Qur'an and al-Hadith.